Prevalence of dementia and mild cognitive impairment among the older prisoner population in England and Wales: a cross-sectional study - Richard Emsley; Alistair Burns; Jane Senior; Roger Webb; Katrina Forsyth; Matthew J Carr; Baber Malik; Leanne Heathcote; Laura Archer-Power; Rachel Domone; Salman Karim; Adrian Hayes; et al. (BMJ Open)
Objectives To estimate the prevalence of dementia and mild cognitive impairment (MCI) in the older prisoner population in England and Wales and to establish risk of harm to self and others, activity of daily living needs and social networks of prisoners with likely MCI and dementia.Design We screened 869 older prisoners (aged 50 years and older) using the Montreal Cognitive Assessment (MoCA). Participants testing positive on the MoCA (≤23) were interviewed using the Addenbrooke’s Cognitive Examination, Third Revision (ACE-III) and a range of standardised assessments were used to assess risks of externalised violence and of self-harm; activities of daily living needs; mental health needs; history and symptoms of brain injury (if applicable) and social networks.Setting The sample was drawn randomly from women’s prisons (n=10) and a representative range of adult men’s prisons (n=11) across England and Wales.Participants Participants were aged 50 or over and resident in one of the participating prison establishments on the study’s census day.Main outcome measure ACE-III.Results We recruited 596 men and 273 women prisoners. Across the whole sample of older prisoners, the prevalence of dementia was 7.0% (95% CI 5.5%, 8.9%) (when weighted for sex and age), with the highest prevalence found among prisoners aged 70 years and older at 11.8% (95% CI 8.0%, 17.1%). The prevalence of dementia for men was 7.0% (95% CI 5.2%, 9.4%) and for women was 6.0% (95% CI 3.8%, 9.5%). Only two individuals (3%) who screened positively on the MoCA had a diagnosis of dementia in their prison healthcare notes, suggesting current under-recognition. The prevalence of MCI was 0.8% (95% CI 0.4% to 1.7%, weighted by age). Of those who screened positively on the MoCA, 32 (46%) participants had a high or very high risk of harm to self or others, and 70 (35%) had no friends with whom they could talk to about private matters or to call on for help (n=35, 50%).Conclusions Approximately 1020 older adults living in prison have symptoms of likely dementia, and service provision for this group is inadequate.